2020
DOI: 10.1024/1662-9647/a000220
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Focus in the Emotional Autobiographical Memories of Older and Younger Adults

Abstract: Abstract. The present study examined the interpersonal focus within autobiographical memories (AMs) of older and younger adults from the perspective of socioemotional selectivity theory (SST). Specifically, we measured interpersonal focus directly through rater codings (relational vs. individual focus) and social word use, and indirectly through personal pronoun use. Forty-five older ( Mage = 76.76) and 25 younger ( Mage = 18.64) adults recalled positive and negative AMs, which were then coded and processed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…are probably more frequent than sad relationship events (e.g., conflicts). This result is also consistent with a recent study highlighting that the memories of older adults contained more relationship sequences when collecting positive memories compared to negative ones (Polsinelli et al, 2020).…”
Section: Interactions and Correlations Between Sdms' Dimensionssupporting
confidence: 93%
“…are probably more frequent than sad relationship events (e.g., conflicts). This result is also consistent with a recent study highlighting that the memories of older adults contained more relationship sequences when collecting positive memories compared to negative ones (Polsinelli et al, 2020).…”
Section: Interactions and Correlations Between Sdms' Dimensionssupporting
confidence: 93%
“…Since there was no significant association with any of the subscales of KIIP-SC, which collects responses to difficulties in interpersonal relationships, the RF was considered insufficient to identify problematic or maladaptive interpersonal schemas. However, the reported interpersonal SDM’s frequency is suggested to be important in identifying individuals’ self-image related to interpersonal relationships [ 40 , 41 ]. It is thought that the predictive validity of this index could be examined through further research, rather than immediate discarding.…”
Section: Discussionmentioning
confidence: 99%
“…Relationship frequency (RF): As several researchers have revealed, the frequency of reporting SDMs for interpersonal relationships was thought to be important in identifying the self-image or adaptive behavior of individuals related to interpersonal relationships [ 40 , 41 ]. When the content of SDM included interpersonal relationships in each category, a score of 1 was coded.…”
Section: Methodsmentioning
confidence: 99%
“…Polsinelli, Rentscher, Glisky, Moseley, and Mehl (2020) examined the interpersonal focus of negative and positive memories of older adults from the perspective of socioemotional selectivity theory. Consistent with that theory, they found that the positive memories of older adults were more interpersonally focused (and less self-focused) compared to their negative memories and to the positive memories of younger adults.…”
mentioning
confidence: 99%
“…Manual coding is a commonly used method in autobiographical memory research, although it is a laborious and demanding task. Polsinelli et al (2020) used a computerized text analysis tool, the Linguistic Inquiry and Word Count (LIWC), in addition to manual coding in order to bolster their methodology. Social scientists have started investing in the automatization of coding procedures by collaborating with computer scientists to use machine learning to automatically code text (Demiray, Luo, Tejeda-Padron, & Mehl, in press).…”
mentioning
confidence: 99%